Opening the tablet box : Near Eastern studies in honor of Benjamin R. Foster - Foster, Benjamin R. 1945-; Melville, Sarah C.; Slotsky, Alice L. (Culture and History of the Ancient Near East, 2010)
This volume is a scholarly tribute to Benjamin R. Foster, Laffan Professor of Assyriology and Babylonian Literature and Curator of the Babylonian Collection at Yale University, from some of his students, colleagues, and companions, in appreciation of his outstanding achievements and in thanks for his friendship. Reflecting on the remarkable breadth of the honoree's research interests, the twenty-six original papers in this Festschrift cover a wide range of topics in ancient Near Eastern and Egyptian literature, economic and social history, as well as art and archaeology.